Benefits of spirituality for the resignification of the patient in palliative care: Literature review - Silva, André Luiz Barreto Oliveira da; Câmara, Barbara de Siqueira; Silva, Cássia Ellen da Conceição; Brito, Mariana Queiroz; Paula, Luiza Helena Andrade de; Freitas, Vera Lúcia (Seven Editora, 2023)
Objective: This study aims to present the benefits of spirituality for the resignification of the illness of patients in palliative care. Methodology: This is a qualitative study of integrative review (IR) by reading articles published between the years 2018 to 2022, available in full online and free, in Portuguese, Spanish, and English languages. Articles that specifically worked on the topic of spirituality and palliative care. 239 studies were identified and 186 were excluded by title and abstract. 48 of the full studies were assessed for eligibility, 41 were excluded for being paid and 7 articles were included for qualitative synthesis. Results: The articles presented benefits, improved quality of life, and perceived personal significance of one’s life. They pointed out that there was the attainment of peace and the discovery of inner strength. The patients obtained relief from pain, and increased faith, hope, and well-being. Conclusion: It was observed that spirituality brings benefits to patients in palliative care during the entire process of facing death, regardless of the phase in which they are within this process. DOI:https://doi.org/10.56238/devopinterscie-238